Is the risk of product market predation a cost of disclosure? - Bernard, Darren (Journal of Accounting and Economics, 2016)
Competitors engage in product market predation when they lower prices or increase expenditures on nonprice competition with the goal of forcing a rival to exit. This study provides evidence that financially constrained firms avoid financial statement disclosure to mitigate predation risk. The empirical tests examine German private firms, most of which failed to comply with financial statement public disclosure requirements until an enforcement change increased noncompliance costs. The evidence shows more financially constrained firms were more likely to avoid disclosure until the change. Results from cross-sectional and supplemental analyses are consistent with predation risk driving this relation.